The Effect of Katuk (Sauropus androgyrus) Leaves Administration to the Size of scrotal Circumference of Male lokal Kacang Goats - Rahmat Yusman; Teuku Reza Ferasyi; Muttaqien Muttaqien (Jurnal Medika Veterinaria, 2014)
The purposed of this study was to test the administration effects of katuk leaves to the size of scrotal circumference of male local kacang goat. This study used 15 male local kacang goats with the age of +1,5 year old. These animals were divided into three groups,5 animals each and acclimatized for 2 weeks. The control group (P0) was given distilated water, group P1 was administered with katuk leaves powder at the dose of 7.44 g/head/day and group P2 was administered with katuk leaves powder at the dose of 14.88 g/head/day. All treatments were given per oral twice a day (at 07.30 AM and 16.30 PM) for 35 days, consecutively. All animals were given various pastures and grasses as well as water ad libitum every day. Pre and post treatment, all animals from each group were measured for the scrotal circumference using vernier caliper. Data were analyzed using ANOVA. The result showed that the average of scrotal circumference on P0, P1, and P2 were 1.99+1.00, 2.75+0.01, and 2.76+0.01 cm. There was significant different (P0.01) on the size of scrotal circumference between all groups. In conclusion, the administration of Sauropus androgyrus leaf powder increases the size of scrotal circumference of male local goat.Key words: scrotal circumference, willow leaf, male local goat